1987
DOI: 10.1021/bi00387a002
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-sensitive mutations of bacteriophage T4 lysozyme occur at sites with low mobility and low solvent accessibility in the folded protein

Abstract: Twenty-five different temperature-sensitive point mutations at 20 sites in the lysozyme gene of bacteriophage T4 have been identified. All of the mutations alter amino acid side chains that have lower than average crystallographic thermal factors and reduced solvent accessibility in the folded protein. This suggests that the amino acids with well-defined conformations can form specific intramolecular interactions that make relatively large contributions to the thermal stability of the protein. Residues with hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
142
1

Year Published

1989
1989
2007
2007

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 263 publications
(158 citation statements)
references
References 34 publications
15
142
1
Order By: Relevance
“…Other evidence in support of this idea in- cludes the demonstration by Sauer and coworkers that amino acids in a given protein can have a low "information content" (Bowie et al, 1990). Also, amino acid substitutions of mobile solvent-exposed residues on the surface of a protein generally have little effect on stability (Hecht et al, 1986;Alber et al, 1987). In experiments parallel to those reported here, Heinz et al (1992) have constructed a mutant lysozyme with 10 consecutive alanines (residues 40-49) in a different a-helix and have shown that that variant also folds normally.…”
Section: Tolerance Of a Polyalanine Helixmentioning
confidence: 70%
“…Other evidence in support of this idea in- cludes the demonstration by Sauer and coworkers that amino acids in a given protein can have a low "information content" (Bowie et al, 1990). Also, amino acid substitutions of mobile solvent-exposed residues on the surface of a protein generally have little effect on stability (Hecht et al, 1986;Alber et al, 1987). In experiments parallel to those reported here, Heinz et al (1992) have constructed a mutant lysozyme with 10 consecutive alanines (residues 40-49) in a different a-helix and have shown that that variant also folds normally.…”
Section: Tolerance Of a Polyalanine Helixmentioning
confidence: 70%
“…Mutations that substantially destabilize T4 lysozyme tend to be restricted to those amino acids that have the lowest thermal motion (Alber et al, 1987;Matthews, 1993). Takano et al (1995) have also suggested that there might be an inverse correlation between mobility and destabilization for Ile Val substitutions in human lysozyme.…”
Section: Packing Density and Thermal Motionmentioning
confidence: 99%
“…These include T59S (Bell et al, 1992), T152S (Alber et al, 1987a;Dao-pin et al, 1991), T157S (Alber et al, 1987b), A98T (Alber et al, 1987a), A146T (Alber et al, 19861, and A160T (Alber et al, 1987a). All appear to be temperaturesensitive to a greater or lesser degree, showing that there is no reason to believe that threonine to serine (or alanine to threonine) substitutions are intrinsically stabilizing.…”
Section: Discussionmentioning
confidence: 99%